'Aprendiz de Proust': Gilberto Freyre in Search of a Lost Past and a Renewed Future in Aventura e rotina. Issue 8 (14th September 2019) - Gonçalves Miranda, Rui
Abstract: The function of the self-proclaimed 'Proustian' traits of Gilberto Freyre's work will act as the point of departure for a critique of Freyre's conception of his non-fiction works, namely the travelogue Aventura e rotina (1953). As Freyre strategically frames a number of authors as the precursors to his own work in search of the intimate past of Brazil and/or of the almost lost presence of the Portuguese overseas, he concomitantly deploys disparate literary and historical/sociological structures and methods to suit particular aims. When accounting for this process, there are benefits in taking up Freyre's claim that his non-fiction work bears a 'literary character' and his self-definition as, first and foremost, a 'escritor literário' at face value. Freyre's much lesser- known 'semi-novela' Dona Sinhá e o filho padre (1964) and respective epilogue will provide insight into Freyre's fusion of, and confusion between, the historical and the literary. The postulation, in Aventura e rotina, that Fernão Mendes Pinto was a precursor to Proust goes hand in hand with the establishment of a teleological line of what Brazil should be, as Freyre conveniently fashions himself as the writer who 'proustianamente' glimpses ('entrever') the supposedly underlying unity behind and beyond the diversity and disparity of the 'lusotropical' world.